2011
DOI: 10.2139/ssrn.1816428
|View full text |Cite
|
Sign up to set email alerts
|

Le Ciblage d’Inflation: Un Essai de Comparaison Internationale

Abstract: La politique de ciblage d'inflation est un régime monétaire qui vise l'inflation. Sa pratique a été marquée par une grande stabilité observée aux débuts des années 90 et 2000. Un débat émerge sur l'efficacité et la performance économique de ce régime. De nombreuses recherches se sont intéressées à cette question sans pouvoir pour autant parvenir à un consensus ultime. L'objectif de ce papier est de contribuer à ce débat en clarifiant l'origine de ce régime monétaire et en proposant, par la suite, notre propre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Central Bank independence, transparency of policy maker's actions, credibility of policy maker's actions and communication.22 Choice of price index, price target announcement, target horizon announcement, target width and communication. For more details seeFtiti and Goux (2011).…”
mentioning
confidence: 99%
“…Central Bank independence, transparency of policy maker's actions, credibility of policy maker's actions and communication.22 Choice of price index, price target announcement, target horizon announcement, target width and communication. For more details seeFtiti and Goux (2011).…”
mentioning
confidence: 99%
“…This diversification, as Berg et al (2003: p. 25) have pointed out in the case of Latin American countries, is a sensible solution for a monetary union, since the relevance of the choice of an economic and monetary union depends on the structure of trade, the similarity of business cycles in the different countries, financial factors and political and institutional considerations. In the context of a monetary union project, authors agree on the importance of price stability for the central bank (Brociner, 1993;Ftiti & Goux, 2011). Although the effectiveness and economic performance of the 7 inflation-targeting policy are not accepted by all authors, its practice on the other hand was marked by great stability observed in the early 1990s and 2000s (Ftiti & Goux, 2011: p. 1).…”
mentioning
confidence: 99%